Religion, Faith, Theology and Spirituality - Coupeau Dorronsoro SJ, José Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
These pages argue in favor of the place that Spiritual theology retains within the theological curriculum. They lead the reader through a threefold telescopic and dialectic process, which compares spirituality with religion in general, with the Christian religion in particular and with other theological studies integrating the baccalaureatus in theologia. This process allows for a series of oppositions such as a relational identity versus concrete practicing, true devotion versus devotional endeavors, and a way of life versus mere theological reflection. The article concludes by showing the supplementary character of this theological discipline in relation to the dogmatic and moral disciplines. It points, however, in the direction of the preliminary and critical theological character that Spiritual Theology may bear in connection to those disciplines, for it concerns with the believer’s experience, which is the fountain spring –so to speak– of any consequent theological discourse.
Keywords: spirituality; spiritual experience; spiritual subject; critical speech; spiritual practices; spiritual process; mystagogy; devotion